THE CHANGES IN ENSURING THE MILITARY SECURITY ACTIONS - Boldbaatar Zagdsuren, (International Journal of Innovative Technologies in Social Science, 2024)
The security and military-strategy landscape of countries worldwide is undergoing significant changes. Following these changes, traditional hard power policies have evolved in terms of content and manifestation, giving rise to the concept of a "New cold war." This new approach utilizes information technology, economic actions, and political pressure methods and tactics, significantly decreasing the budget and costs associated with traditional warfare.The new Cold War approach emphasizes the use of new technologies, information space, and political and economic actions. As global defense costs rise, the strategy's content and objectives are constantly evolving. The traditional hard power policy has evolved into a new Cold War.This article will specifically consider the new trends in the changes in military affairs and I will provide my opinion and conclusions. The initial phase of the emerging Cold War is primarily unfolding in the realm of information in cyberspace. It focused on strategically targeting social and political arenas with goal of the weakening the societal and economic structures.The countries around the world view basis of the potential threats as information warfare, psychological operations, economic coercion, internal governance challenges, transnational criminal organizations, and environmental degradation influenced by external factors.In this reason, the military strategy and security policy will prioritize anticipating and preventing risks. The science of security has evolved to focus on potential challenges and risks, regulating development policies to ensure existence. Due to these evolving factors, the field of security has transformed into a science of Security of existence, with a greater emphasis on anticipating challenges and risks and shaping development policies.